Industrial training report: Jakel Trading Sdn Bhd / Ilyas Ibrahim - Ibrahim, Ilyas (Perpustakaan Tengku Anis, 2019)
Starting from the February 2019 until June 2019, trainee has been placed at the Information Technology department in JAKEL Trading SDN. BHD. In short period of times the trainee were also given task that are related to other department due to the business nature of the organization. A lot of knowledge and experience were exposed to the trainee which is a very rare experience for an internship student. The system that were exposed to the trainee are two kind of system which is inventory system which were called Jakel Online and Jakel Store which is a website. Jakel Online system is an inventory system which are still updated where the function is to detect the current stock of the goods that are in the outlets and warehouse online. Through the system it is easier for Jakel to segregate the goods in the future just by look at the system. Second is the Jakel Store website where it is the a platform for people to shop online. In the website consumer can choose what item they want, what colour the consumer want to choose and free gift were also included.